How ecosystem services are measured and why it matters for Florida - Charles Wallace; Anna Braswell; Mysha Clarke; Andrew Ropicki; Tara Wade; Frank Asche; Ashley Smyth; Armando Ubeda; Ed Camp (EDIS, 2023)
Florida has many ecosystems that are thought of as especially important such as springs, coasts, dry prairies, and the Everglades. One of the ways importance is measured is through value. The term ecosystem services describes the benefits ecosystems and their components provide humans. This publication describes some of the ways to measure ecosystem services and explains how the different approaches to assess ecosystems might be selected, depending on what is most important to the user. This publication should help Extension and outreach agents, as well as agency personnel better understand ecosystem services values and explain them to the public. It should also help interested members of the public who wish to learn more about ecosystem services for themselves.